Migralepsy: from hypotheses to controversies - Silva, Pedro Henrique da; Santos, Gabriela Silveira dos; Strapacao, Andre Luis; Pereira, Kleber Fernando (Headache Medicine, 2024)
The review aims to clarify what is known or assumed about migralepsy, from its causes to its controversial classification, as well as providing a clearer and more critical understanding of migralepsy, helping to distinguish between migraine with aura and epileptic seizures.